Assessing Symptom Accommodation of Social Anxiety Symptoms Among Chinese Adults: Factor Structure and Psychometric Properties of Family Accommodation Scale Anxiety—Adult Report - Lou, Congmei; Zhou, Xiaolu; Lebowitz, Eli R.; Williams, Laurel L.; Storch, Eric A. (Frontiers in Psychology, 2020)
Objective Symptom accommodation is an important interpersonal construct associated with more severe symptoms, lower levels of functioning, and worse treatment outcomes across various mental health conditions, including social anxiety. Research on this phenomenon is surprisingly absent in Chinese culture, where interpersonal relationships are highly emphasized. This may be due to the absence of a valid Chinese symptom accommodation measure for individuals with social anxiety symptoms. The current study aimed to examine the factor structure and psychometric properties of the Family Accommodation Scale Anxiety—Adult Report (FASA-AR) in Chinese adults. Methods Three hundred and seventy-five Chinese undergraduate students with social anxiety symptoms completed a battery of self-report measures assessing symptom accommodation in relation to social anxiety symptoms and related impairments, as well as overall symptoms of anxiety and depression. Results Confirmatory factor analysis supported a two-factor model of symptom accommodation, with factors named Participation in symptom-related behaviors and Modification of functioning. The multiple indicators multiple causes model indicated the indicators of the FASA-AR, mainly the participation in symptom-related behaviors subscale, were not invariant across gender. Internal consistency for the FASA-AR total score and subscale scores was good. Convergent validity of the FASA-AR was evidenced by significant positive association with ratings of social anxiety symptoms, social anxiety related impairments, and anxiety symptoms. Divergent validity was supported by non-significant relation with depression symptoms. Nearly all participants (94.7%) endorsed being accommodated to some extent in the past month. Conclusion Symptom accommodation is an important construct and is related to social anxiety symptoms among Chinese adults. The FASA-AR demonstrated a clear two-factor latent structure and possessed good psychometric properties that can validly and reliably assess symptom accommodation of social anxiety among Chinese adults.